OVERVIEW OF THE ELECTROCHEMISTRY AND ELECTROANALYTICAL CHEMISTRY IN BRAZIL - Boldrin Zanoni, Maria Valnice [UNESP]; Borges, Alessandro Santos [UNESP]; Benedetti, Assis Vicente [UNESP]; Yamanaka, Hideko [UNESP]; Taboada Sotomayor, Maria del Pilar [UNESP]; Bessegato, Guilherme Garcia [UNESP]; Stradiotto, Nelson Ramos [UNESP]; Paiva e Silva Zanta, Carmem Lucia de; Andrade, Adalgisa Rodrigues de (Soc Brasileira Quimica, 2017)
Electrochemistry and Electroanalytical chemistry play an important role to face the challenges of the contemporary world. They have contributed to the advance of the scientific development of our country, helped to promote economic and social progress as well as cultural dissemination. These areas have greatly contributed to the knowledge about thermodynamics and kinetics of the electron transfer reactions, energy conversion, synthesis and modification of compounds, corrosion, and development of fast, sensitive, and selective analytical methods. This work presents an overview of the areas by analyzing the technical and scientific papers produced in Brazil on these subjects, and the analysis of the Brazilian scientific societies that were formed and consolidated, which have contributed to spread the scientific knowledge. The improvement of these areas can be attributed to the good quality of the human resources formed during long time as well as the growing of distribution of research groups in different regions of the country. The success/future of these areas are associated with good academic/scientific education, low cost of instrumentation, formation of networks of excellence between researchers, and large cooperation projects that improved with the sharing of ideas, technologies, infrastructure, and equipment. All of which has contributed to strengthening consolidated and emerging graduation programs.
Keywords: Trends in Electrochemistry; Electroanalytical chemistry assessment; research in Electrochemistry and Electroanalysis